Learning to read through google classroom for undergraduate EFL students in Indonesia - Tririndi Krisna Nuralim; Erna Dwinata (SALEE: Study of Applied Linguistics and English Education, 2022)
Google Classroom is one of the contemporary popular online learning media. Through this platform, students can continue to carry out online learning. Google Classroom can be used for assignments and information, submitting assignments, and providing assessments. This study was conducted to determine whether the use of Google Classroom is effectively used to teach students' reading skills. This study uses quantitative research methods with pre-experimental design. The sample of 11 students from second semester students of English Education Department in an Indonesian university. Samples were taken using purposive sampling technique. In this study, data collection was used using tests. This study uses statistical calculations using IBM statistics 28.00 to determine the significance value. The result of the calculation is that the significance value of 0.039 is smaller than 0.05, so it can be concluded that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. This means that there is a significant effect after using Google classroom to teach reading. Thus, it can be concluded that the use of Google Classroom in learning to read for first year tertiary students is effective.